2020
DOI: 10.1093/braincomms/fcaa216
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of hemispheric structural network change as a function of location and size of glioma

Abstract: Gliomas are neoplasms that arise from glial cell origin and represent the largest fraction of primary malignant brain tumours (77%). These highly infiltrative malignant cell clusters modify brain structure and function through expansion, invasion and intratumoral modification. Depending on the growth rate of the tumour, location and degree of expansion, functional reorganization may not lead to overt changes in behaviour despite significant cerebral adaptation. Studies in simulated lesion models and in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…This result suggests that higher WHO grade gliomas are more likely to impair the cortico-subcortical connections regardless of their location, thus further reinforcing the idea that patterns of altered structural connectivity depend on the WHO grade (10,69). As earlier studies have demonstrated local effects of gliomas on their surrounding microstructural integrity of the WM (70,71), we aimed at investigating whether glioma locations may affect unique subsets of nodes and edges in the ipsilesional network. While gliomas affect brain regions and connections near the lesion, brain connectivity changes may also occur distally from the lesion, either because of the resulting local dysconnectivity or as a neuroplasticity mechanism taking place during tumor growth.…”
Section: Glioma-related Hemispheric Differencesmentioning
confidence: 62%
See 2 more Smart Citations
“…This result suggests that higher WHO grade gliomas are more likely to impair the cortico-subcortical connections regardless of their location, thus further reinforcing the idea that patterns of altered structural connectivity depend on the WHO grade (10,69). As earlier studies have demonstrated local effects of gliomas on their surrounding microstructural integrity of the WM (70,71), we aimed at investigating whether glioma locations may affect unique subsets of nodes and edges in the ipsilesional network. While gliomas affect brain regions and connections near the lesion, brain connectivity changes may also occur distally from the lesion, either because of the resulting local dysconnectivity or as a neuroplasticity mechanism taking place during tumor growth.…”
Section: Glioma-related Hemispheric Differencesmentioning
confidence: 62%
“…Reduced global and local efficiency reflect the impairment of information transfer across different regions of derived networks, which is likely linked to the pathological involvement of both long- and short-range connections. In contrast with these findings, a recent publication showed increased global and local efficiency in the ipsilesional hemispheric network, identifying unique sets of nodes with changes in network efficiency depending on lesion location ( 71 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was previously described that different kinds of neurological disorders, such as brain tumors lead to deviations in the brain’s functional network (Cho et al, 2021; D’Souza et al, 2021; Huang et al, 2014; Hyder et al, 2021; Na et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of this is to achieve the research goal quickly and cost effectively. Previous retrospective studies have utilized existing DWI data sets to investigate late radiation‐induced damages after focal radiotherapy, 1 hemispheric structural network changes as a function of location and size of glioma, 2 and even the relationship between reading performance and white matter (WM) alteration and reorganization in neurosurgical patients 3 . In addition, as more and more archived data become publicly available, research can be conducted efficiently if the data can be processed in an appropriate way.…”
mentioning
confidence: 99%